2021
DOI: 10.1021/acssuschemeng.1c05676
|View full text |Cite
|
Sign up to set email alerts
|

Role of Phosphorus and Iron in Particle Adhesiveness at High Temperatures Using Synthetic Ashes

Abstract: During sewage treatment, phosphorus (P) is concentrated in sewage sludge, and the sludge is incinerated to produce P-concentrated ash particles. The P-containing ash particles possess high adhesiveness at high temperatures, which can cause problems for the incineration plants. Phosphorus is considered a key element for inducing ash particles adhesiveness; however, the mechanistic details remain unclear. The present study clarified the role of P in particle adhesion at high temperatures using synthetic ashes, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…2,3 Numerous additives have been developed for this purpose. 3,12−25 In previous reports, 12,13 we demonstrated the chemical efficacy of Al on the suppression of particle adhesion induced by alkali metals such as Na and K using coal ash and synthetic ashes containing alkali metals. Particle adhesion was quantified as the tensile strength of the powder bed using a previously developed device to measure the strength.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…2,3 Numerous additives have been developed for this purpose. 3,12−25 In previous reports, 12,13 we demonstrated the chemical efficacy of Al on the suppression of particle adhesion induced by alkali metals such as Na and K using coal ash and synthetic ashes containing alkali metals. Particle adhesion was quantified as the tensile strength of the powder bed using a previously developed device to measure the strength.…”
Section: Introductionmentioning
confidence: 76%
“…Alkali metals in ash can react with SiO 2 and Al 2 O 3 , which are the main components of ash and bed materials in a fluidized bed furnace. , As a result, compounds with a melting point lower than those of SiO 2 and Al 2 O 3 form and subsequently melt at the operating temperatures. These compounds form “liquid bridges” between ash particles and act as adhesives, thereby inducing adhesion. , Techniques to suppress this adhesion include using additives to alter the composition of the ash and increase its melting point through chemical effects. , Numerous additives have been developed for this purpose. , In previous reports, , we demonstrated the chemical efficacy of Al on the suppression of particle adhesion induced by alkali metals such as Na and K using coal ash and synthetic ashes containing alkali metals. Particle adhesion was quantified as the tensile strength of the powder bed using a previously developed device to measure the strength .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthetic ash was prepared according to the reported method herein. ,, In brief, silica microparticles were used as carriers, whose surfaces were coated with sodium or potassium. The oxalate salts were used as the sodium or potassium sources and were mixed with silica microparticles in deionized water.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…We have prepared synthetic ashes composed of P and SiO 2 (P-SiO 2 ), and studied their adhesion behavior related to phosphorus (Figure 1b). 28,36 It was found that the tensile strength of P-SiO 2 increased proportionally with increasing P concentration. It was indicated that high concentration of phosphorus in ash can cause trouble in thermochemical conversion plants.…”
Section: ■ Introductionmentioning
confidence: 99%